Patrilocality in the Harivamsa’s Visnuparvan - Brodbeck, Simon (Religions of South Asia, 2021)
This article suggests that the principle of patrilocality, as espoused by Krsna and Baladeva, can be applied as an interpretive frame to almost all of the narrative material that Vaisampayana presents to Janamejaya in the Harivamsa’s Visnuparvan (Hv 46–113), and that the principle of patrilocality is thus a key theme of the Visnuparvan, with Krsna and Baladeva as its heroes. This suggestion is supported by an overview of the Visnuparvan’s narrative from beginning to end, in eleven sections which repeatedly feature—or can be interpreted to feature—conflict with in-law families about where a couple will have children, and which of the two families the children will be raised for.